2017
DOI: 10.5414/cn109032
|View full text |Cite
|
Sign up to set email alerts
|

Survey among nephrologists in Germany: current practice and management of pregnant women on dialysis

Abstract: Our survey demonstrates that the practice of nephrologists in treating pregnant women on dialysis differs significantly. These findings highlight the need for European guidelines to standardize the care of pregnant dialysis patients.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Though we did not specifically email private practice individuals, this may signal nonresponse bias from those who did not fill out the survey possibly due to a lack of interest or knowledge in the topic. Within the CSN network, the response rate was 17%, which is comparable to a prior web-based survey of nephrologists regarding management of sex hormone status in women with CKD (21%) [13] and larger than a prior survey of German nephrologists (10%) [14]. To better contextualize our convenience sample, we compared the Canadian survey respondent characteristics to the Canadian Medical Association Nephrologist profile, which contains demographic data of every registered nephrologist in Canada and was updated in August 2018 [35].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Though we did not specifically email private practice individuals, this may signal nonresponse bias from those who did not fill out the survey possibly due to a lack of interest or knowledge in the topic. Within the CSN network, the response rate was 17%, which is comparable to a prior web-based survey of nephrologists regarding management of sex hormone status in women with CKD (21%) [13] and larger than a prior survey of German nephrologists (10%) [14]. To better contextualize our convenience sample, we compared the Canadian survey respondent characteristics to the Canadian Medical Association Nephrologist profile, which contains demographic data of every registered nephrologist in Canada and was updated in August 2018 [35].…”
Section: Discussionmentioning
confidence: 63%
“…Figure 1 presents a flowchart of the survey development and dissemination. Survey question construction was grounded in a comprehensive literature review of qualitative and quantitative studies of women’s health in CKD [9,10,11,12,13,14]. Three main themes arose: participant characteristics and fellowship training, current clinical practices, and confidence levels in counseling and managing women’s health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement in results recorded with daily, extended-hours dialysis not only allowed a more permissive attitude towards pregnancy in dialysis, but is also leading to a more positive attitude towards pregnancy in advanced CKD, often previously discouraged for the fear of needing to start dialysis during gestation [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Dialysismentioning
confidence: 99%
“…[3] In a survey among nephrologists in Germany, about 45% of the doctors routinely provided contraception counseling and pregnancy guidance on the women undergoing MHD, 22% of them would suggest terminating pregnancy after the conception, whereas only 40% of all the respondents felt confident in dealing with pregnant women on dialysis. [4] Similarly, the survey in America indicated that 46% of nephrologists and their staffs offered contraception counseling, 37% stated they would recommend termination of pregnancy in dialyzed women, and 30% felt some uncomfortable to treat dialyzed pregnant women. [5] On the basis of these results, more attention should be paid in the diagnosis and treatment of pregnancy in women on dialysis.…”
Section: Discussionmentioning
confidence: 99%